2023
DOI: 10.3389/fmicb.2023.1185806
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with Chinese herb ultrafine powder improves intestinal morphology and physical barrier function by altering jejunal microbiota in laying hens

Abstract: IntroductionChinese medicinal herbs play important roles in anti-inflammatory, antioxidant, and antibacterial activities. However, the effects of Chinese herb ultrafine powder (CHUP) on laying hens still need to be elucidated. Therefore, this study aimed to evaluate the effects of dietary CHUP supplementation on jejunal morphology, physical barrier function, and microbiota in laying hens.MethodsA total of 576 Xinyang black-feather laying hens (300 days old) were randomly assigned into eight groups, with eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Currently, limited studies have investigated the effects of Chinese herbal mixtures on intestinal microbiota. The beneficial functions of Chinese herbal mixtures are attributed to their active ingredients such as polysaccharides, polyphenols, and organic acids [59,60]. In the present study, the TCM was found to be rich in polysaccharides, which have been shown to modify the composition and diversity of intestinal microbiota, including increasing the abundance of Lactobacillus in mice [45].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Currently, limited studies have investigated the effects of Chinese herbal mixtures on intestinal microbiota. The beneficial functions of Chinese herbal mixtures are attributed to their active ingredients such as polysaccharides, polyphenols, and organic acids [59,60]. In the present study, the TCM was found to be rich in polysaccharides, which have been shown to modify the composition and diversity of intestinal microbiota, including increasing the abundance of Lactobacillus in mice [45].…”
Section: Discussionmentioning
confidence: 50%
“…In the present study, the TCM was found to be rich in polysaccharides, which have been shown to modify the composition and diversity of intestinal microbiota, including increasing the abundance of Lactobacillus in mice [45]. The TCM also contains high concentrations of polyphenols, which have been shown to regulate the intestinal microbial composition of animals and maintain intestinal health [60]. For instance, Wang et al [17] demonstrated that tannic acid, a type of could alleviate obesity symptoms by reducing the ratio of Firmicutes/Bacteroides in weaned piglets.…”
Section: Discussionmentioning
confidence: 54%